Impact of the ‘Nola J Pender’ Health Promotion Model Towards the Level of Community Compliance in Implementing COVID-19 Health Protocols - Reza Indra Wiguna; Haris Suhamdani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: Indonesia is facing COVID-19 waves in almost all provinces. Based on data from the COVID-19 Response Acceleration Task Force, there were 57 districts with a compliance level of wearing a mask by less than 60%, while 51 districts had a compliance level of keeping distance and avoiding crowds by less than 60%. Objective: The aim of this study is to analyze the effect of the Health Promotion Model (HPM) in increasing people’s compliance level on the implementation of COVID-19 health protocols. Methods: Quasi-experiment with a single-group interrupted time-series design was conducted in June-September 2021 in West Lombok district and Central Lombok district, West Nusa Tenggara Province. The samples were 326 respondents from purposive sampling with criteria: adult group or elderly of the healthy category and not being positively confirmed of COVID-19. Results: There was a significant effect of HPM in increasing people’s compliance level on the implementation of the health protocols (5M) measured by the Wilcoxon Signed Rank Test (p-value <0,05). The health protocols (5M) included wearing a mask (p=0,000), keeping distance (p=0,000), cleaning hands (p=0,000), avoiding crowds (p=0,000), and reducing mobility (p=0,000). Conclusion: The Health Promotion Model (HPM) is a strategy to conduct health promotion activities that can influence the attitudes and behaviors of community groups marked by increasing knowledge and awareness of people in the Lombok area for the implementation of the 5M COVID-19 health protocols.